Towards the automation of attendance control: improving administrative efficiency in higher education in Ecuador - Narváez-Quintero, José Luis; Meza, Josueth; Andrade-Chaguaro, Cristian; Díaz Ayala, Joffre Omar (Acta Universitaria, 2026)
Attendance control for teachers is a crucial component in the educational system, but it is facing significant challenges due to manual methods that generate errors and waste time. The implementation of technologies, such as biometric systems and human resource management tools, presents an effective solution to optimize this process. Information and communication technologies (ICT) allow for more precise monitoring of performance, improving efficiency and decision-making. However, resistance to change and a lack of technical expertise are both obstacles that must be overcome. Automation not only enhances human talent management, it also contributes to a more effective and sustainable educational environment. Continuous evaluation of the impact of these technologies is essential to ensure educational quality and continuous improvement.